Study acute toxicity of 4-(R-amino)-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol in vivo - A. A. Safonov (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Typically, the system is already known are used as the core for a new substance, which have already proved themselves as potential drugs. So one of these is 1,2,4-triazole ring. The purpose was to study acute toxicity of 4-((R-iden)amino)-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiols and identify possible patterns acute toxicity of the chemical structure of indicators derivatives. In the study of acute contact toxicity was used spreadsheet rapid method for Prozorovsky V. B. Analysis of the results of studies acute toxicity of 1,2,4-triazole derivatives showed that all substances are relate to the 4th class of toxicity according to K. K. Sidorov. Their toxicity is in the range 357 ± 28-1 250 ± 220 mg/kg. Introduction in a molecule 4-amino-5-(thiophene-2-ylmethyl)-4H-1,2,4-triazole-3-thiol nitrobenzylidene, dimethylaminobenzylidene, 2-chloro-6-fluorobenzylidene substituent leads to a reduction of acute toxicity to the 566-576 mg/kg. Replacement of 2-chloro-6-fluorobenzylidene radical in a molecule 4-((2-chloro-6-fluorobenzylidene)amino)-5-(thiophene-2-ylmethyl)-4H-1,2,4-triazole-3-thiol at 4-fluorobenzylidene, 3,4-difluorobenzylidene, 4-methoxybenzylidene, 3,5-dimethoxybenzylidene leads to further reduce toxicity. Introduction methyl radical in a molecule 4-(benzylidene)amino)-5-(thiophene-2-ylmethyl)-4H-1,2,4-triazole-3-thiol and 4-((4-fluorobenzylidene)amino)-5-(thiophene-2-ylmethyl)-4H-1,2,4-triazole-3-thiol resulting to increased toxicity. It was established that the most toxic substance among the test compounds is 4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol. Its LD50 is 357 ± 28 mg/kg and the least toxic compound 4-((3,4-difluorbenzylidene)amino)-5-(thiophen-2-ilmethyl)-4H-1,2,4-triazole-3-thiol, LD50 1 250 ± 220 mg/kg.